2023
DOI: 10.1007/s00167-023-07479-9
|View full text |Cite
|
Sign up to set email alerts
|

Partial debridement is the most commonly reported treatment option for mucoid degeneration of the anterior cruciate ligament: a systematic review

Abstract: Purpose To determine clinical outcomes and risks of various management strategies for mucoid degeneration of the anterior cruciate ligament (MD-ACL). Methods Three databases MEDLINE, PubMed and EMBASE were searched from inception to January 29th, 2023 for literature outlining clinical outcomes for various management strategies of MD-ACL. The authors adhered to the PRISMA and R-AMSTAR guidelines as well as the Cochrane Handbook for Systematic Reviews of Interventions. Data on satisfaction scores, visual analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…A wide array of treatments have been described in the current literature, ranging from partial to total excision of the ACL with or without notchplasty [ 2 , 5 , 6 , 8 , 9 , 12 , 22 , 24 , 25 ]. A conclusion drawn from a systematic review conducted by Vivekanantha et al suggests that most authors believe in a non-aggressive method of partial ACL debridement, as there has not been any report of recurrence, and the remaining fibers may prevent instability [ 11 ]. Notchplasty, along with partial debridement, was denounced by several authors, who believed that a thorough debridement of the bulky ACL would remove the impingement [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide array of treatments have been described in the current literature, ranging from partial to total excision of the ACL with or without notchplasty [ 2 , 5 , 6 , 8 , 9 , 12 , 22 , 24 , 25 ]. A conclusion drawn from a systematic review conducted by Vivekanantha et al suggests that most authors believe in a non-aggressive method of partial ACL debridement, as there has not been any report of recurrence, and the remaining fibers may prevent instability [ 11 ]. Notchplasty, along with partial debridement, was denounced by several authors, who believed that a thorough debridement of the bulky ACL would remove the impingement [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the literature is replete with outcomes after partial ACL debridement, only a few authors have reported the clinical outcome after total ACL excision [ 6 , 9 , 12 , 25 ]. Nevertheless, the overall clinical outcome, sans instability, in the systematic review by Vivekanantha et al is comparable in the groups that underwent partial vs. total ACL excision [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation